Resolution Of Non-Performing Loans For Kur Guaranteed By Pt. Jamkrindo Denpasar Branch - Pranoto, Dwi; Wiratny, Ni Ketut; Subawa, I Made Mulyawan (Al-Makki Publisher, 2025)
Kredit Usaha Rakyat (KUR) is one of the government’s programs aimed at empowering Micro, Small, and Medium Enterprises (MSMEs) through the provision of interest subsidies to KUR channeling institutions and guarantee fees to guarantee institutions. One of the institutions that provides guarantees for KUR is PT Jaminan Kredit Indonesia (Jamkrindo). As a guarantor, PT Jamkrindo plays a crucial role in ensuring the sustainability of the KUR program, particularly by facilitating financing for MSMEs that are feasible but not bankable—those that are commercially viable but unable to meet conventional lending requirements such as collateral. However, in practice, many KUR loans face repayment issues and fall into the category of Non-Performing Loans (NPLs). This study aims to analyze the KUR guarantee mechanism and the settlement of NPLs by PT Jamkrindo Denpasar Branch Office. The research employs a normative legal method with a statutory and legal theory approach. The findings indicate that PT Jamkrindo applies an indirect guarantee scheme based on Conditional Automatic Cover (CAC). Nevertheless, the mechanism for subrogation or transfer of claim rights after claim payment lacks strict sanctions for KUR channeling institutions that fail to transfer these rights to Jamkrindo. This regulatory gap may result in financial losses for PT Jamkrindo and create an additional fiscal burden for the state.